2018
DOI: 10.1530/jme-18-0077
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids, antenatal corticosteroid therapy and fetal heart maturation

Abstract: Glucocorticoids are essential in mammals to mature fetal organs and tissues in order to survive after birth. Hence, antenatal glucocorticoid treatment (termed antenatal corticosteroid therapy) can be life-saving in preterm babies and is commonly used in women at risk of preterm birth. While the effects of glucocorticoids on lung maturation have been well described, the effects on the fetal heart remain less clear. Experiments in mice have shown that endogenous glucocorticoid action is required to mature the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 129 publications
0
44
0
1
Order By: Relevance
“…In several studies conducted in both humans and other animals, premature birth was found to be associated with abnormal CM hypertrophy and nucleation and premature cell cycle cessation (Bensley et al 2010(Bensley et al , 2018Aye et al 2017). As a caveat, however, patients in these studies were often treated antenatally and/or postnatally with corticosteroids, which may in turn affect CM maturation (Agnew et al 2017).…”
Section: Initiation Of CM Maturationmentioning
confidence: 99%
“…In several studies conducted in both humans and other animals, premature birth was found to be associated with abnormal CM hypertrophy and nucleation and premature cell cycle cessation (Bensley et al 2010(Bensley et al , 2018Aye et al 2017). As a caveat, however, patients in these studies were often treated antenatally and/or postnatally with corticosteroids, which may in turn affect CM maturation (Agnew et al 2017).…”
Section: Initiation Of CM Maturationmentioning
confidence: 99%
“…Several studies found that P*M CMs possess enhanced protein synthesis to match the high demand for muscle fibers and adenosine triphosphate (ATP) metabolism at high speed [41,42]. AMPK are the major regulator of protein synthesis through mTOR-dependent or -independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, prenatal exposure to glucocorticoids improves cardiovascular function in the newborn immediately after birth [ 163 , 229 , 230 , 231 , 232 ]. Antenatal corticosteroid therapy (ACT) of a potent synthetic glucocorticoid mimics the activity of endogenous glucocorticoids and is prescribed to women to decrease the risk of preterm delivery and to mature fetal organs, including the heart [ 233 ]. The goal of ACT is to improve the survival of preterm infants and decrease neonatal morbidity.…”
Section: Recent Advances In Bioactive Lipids In Cardiac Diseasementioning
confidence: 99%